The rules for transforming a function f(x) into a function g(x) are:
g(x) = a·f(b(x-c)) + d where:
a = vertical cmpress (stretch)
b = horizontal dilation (stretch)
c = horizontal (left/right) shift
d = vertical (up/down) shift
![\begin{gathered} For\text{ F(x) = x} \\ g(x)\text{ = a.f(b(x-c))+d} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7dfuy5ont3ewwop1j9sallw1wsgq8r2au6.png)
![a\text{ = }(1)/(5)\text{ , b = 1 , c = 0 }](https://img.qammunity.org/2023/formulas/mathematics/college/k6dw3f3qxlg06np50dl25wxbzkzmi8sihs.png)
Shift up 7 units means d = +7
![g(x)\text{ = }(1)/(5)x+7](https://img.qammunity.org/2023/formulas/mathematics/college/yo5guzxcn17f9fxow023ff640gj50mdpz8.png)
Hence the correct answer is Option D